(untitled) (Research, Society and Development, 2022)
This review aims to address the main impacts caused by social isolation resulting from the COVID-19 pandemic on the eating habits of some populations. This is a narrative review of the literature carried out in the period of July 2022, built to explain the changes in eating habits caused by the COVID-19 pandemic. The elaboration procedure was divided into 2 stages: First, the research question was defined: What are the main changes observed in the eating habits of populations during social isolation? Then, a search was carried out for articles in the databases for the theoretical discursive promotion about the inquiry. Initially, all titles and abstracts were read, respecting the inclusion and exclusion criteria, resulting in the eligibility of 22 articles to compose the results and discussion of the study. The survey results point out that social distancing measures can encourage consumers to decrease fruit and vegetable consumption and increase consumption of ultra-processed products with excessive sugar, fat and sodium content, with increased intake mainly of red and processed meats, fast food, sweets and refined cereals. In conclusion, in the available literature, dietary practices were one of the most modified in different populations, as a result of circumstances, so that the consumption of unhealthy foods with hypercaloric characteristics and low nutritional value tended to increase to the detriment of homemade food before prevalent.